Phenotypic variability from benign infantile epilepsy to Ohtahara syndrome associated with a novel mutation in SCN2A - Syrbe, Steffen; Mütze, Ulrike (Molecular syndromology, 2016)
Mutations in SCN2A have been associated with benign familial neonatal-infantile seizures (BFNIS) as well as infantile-onset epileptic encephalopathy, such as Ohtahara syndrome (OS). We describe a family with 3 affected individuals carrying the novel SCN2A missense variant c.1147C>G, p.Q383E affecting a residue proximal to the highly conserved selectivity filter in the P-loop of the voltage-gated sodium channel (Nav1.2). All 3 individuals presented with seizures in early infancy. However, there were striking differences in the spectrum of clinical presentations, ranging from BFNIS to OS. A change of ion selectivity of Nav1.2 is considered to be the potential pathomechanism underlying this Nav1.2 channel dysfunction. The observation of benign and severe phenotypes due to an identical mutation within one family contradicts the hypothesis of different modes of inheritance as a mandatory feature discriminating BFNIS from SCN2A encephalopathy.
Gesehen am 26.05.2020